2019
DOI: 10.3847/1538-4357/aaf9ac
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of the Massive Molecular Outflow G331.512-0.103. II. Physical Properties, Kinematics, and Geometry Modeling

Abstract: We present observations and analysis of the massive molecular outflow G331.512-0.103, obtained with ALMA band 7, continuing the work from Merello et al. (2013a). Several lines were identified in the observed bandwidth, consisting of two groups: lines with narrow profiles, tracing the emission from the core ambient medium; and lines with broad velocity wings, tracing the outflow and shocked gas emission. The physical and chemical conditions, such as density, temperature, and fractional abundances are calculated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 63 publications
8
26
0
3
Order By: Relevance
“…The authors interpreted the emission like a high-velocity jet lying almost along the line of sight with an expanding shocked shell/bubble surrounding the driving source, which is observed in projection as a ring of ∼ 5 arcsec in size, at the systemic velocity (∼ -90 km s −1 ). The line J=38-37 of HC3N was also reported towards G331 with ALMA observations (Hervías-Caimapo et al 2019). The authors identified this line as a part of a group of lines (HC3N, SiO, S 18 O, HCO + , and H 13 CN) with broad velocity wings tracing the shocked gas and the outflow, for which a temperature of 160-200 K was derived.…”
Section: The Emission Of Hc3n and Larger Cyanopolyynesmentioning
confidence: 68%
See 1 more Smart Citation
“…The authors interpreted the emission like a high-velocity jet lying almost along the line of sight with an expanding shocked shell/bubble surrounding the driving source, which is observed in projection as a ring of ∼ 5 arcsec in size, at the systemic velocity (∼ -90 km s −1 ). The line J=38-37 of HC3N was also reported towards G331 with ALMA observations (Hervías-Caimapo et al 2019). The authors identified this line as a part of a group of lines (HC3N, SiO, S 18 O, HCO + , and H 13 CN) with broad velocity wings tracing the shocked gas and the outflow, for which a temperature of 160-200 K was derived.…”
Section: The Emission Of Hc3n and Larger Cyanopolyynesmentioning
confidence: 68%
“…This could in turn explain the narrower profile of the HC3N line in the group of lines with broad wings (see fig. 1 from Hervías-Caimapo et al 2019).…”
Section: The Emission Of Hc3n and Larger Cyanopolyynesmentioning
confidence: 99%
“…Given the rather low temperatures derived from the rotational diagrams (T exc ∼ 40 K), the hypothesis of a compact emission arising from a region of 5 is unlikely. Rather, we infer that the CH 3 CCH emission is originated from a cooler gas in the outer envelope of G331, in accordance with other observational works toward star-forming regions (Andron et al, 2018;Hervías-Caimapo et al, 2019;Nagy et al, 2015;Churchwell and Hollis, 1983).…”
Section: Rotational Diagramssupporting
confidence: 92%
“…The molecular outflow/HMC G331.512-0.103 (henceforth G331) is one of the most distinctive HMCs known to date. It is associated with a very rich emission spectrum, including simple hydrocarbons, radical species, and a plethora of complex organic molecules (Merello et al, 2013a,b;Mendoza et al, 2018;Duronea et al, 2019;Hervías-Caimapo et al, 2019).…”
Section: Hot Molecular Coresmentioning
confidence: 99%
See 1 more Smart Citation